Morphostructural and immunohistochemical study for evaluation of nano‐TiO2 toxicity in Armadillo officinalis Duméril, 1816 (Crustacea, Isopoda, Oniscidea). Issue 3 (18th November 2019) - Flaccavento, Alessia; Pecoraro, Roberta; Scalisi, Elena Maria; Messina, Giuseppina; Salvaggio, Antonio; Impellizzeri, Giuliana; Lombardo, Bianca Maria; Brundo, Maria Violetta
Abstract: Invertebrates are precious organisms in order to study environmental pollution. In particular, they appear to be suitable as a bioindicator species for pioneer ecotoxicity studies on new xenobiotics such as nanoparticles. In fact, they are able to absorb nanomaterials scattered in the environment in different ways and it's known the compartmentalization of nano‐sized contaminants in selected tissues and intracellular organelles. Titanium dioxide represents the most used nanoparticulate, destined to become probably ubiquitous in the environment. Recently, some research has been published on the toxic potential of nano‐TiO2 in several animal species. Among all invertebrates, Oniscidean Isopods are the only taxon of Crustaceans that has become completely terrestrial, known as excellent bioindicators and bioaccumulators. They have a digestive gland, the hepatopancreas, which is the location of election for the accumulation of pollutants. For this reason, they are considered efficient animal models to ecological studies. For this study, we collected Armadillo officinalis from Natural Oriented Reserve of "Vendicari" (Sicily, Italy), to evaluate the toxicity of titanium dioxide (TiO2 ) on their hepatopancreas, after a short period of exposure. We conducted morphostructural and immunohistochemistry assays. The results suggested a great capacity of the species of bioaccumulation of nanoparticles in the hepatopancreas, where a strong positivity to the metallothioneins was highlighted. Our study confirms that Oniscidean Isopods, in particular Armadillo officinalis, proved to be an appropriate indicator of pollution in terrestrial ecosystems from nanoparticles. Abstract : Oniscidean Isopods are excellent bioindicators and bioaccumulators. Hepatopancreas represented an excellent detoxification system to nanoparticles. Metallothioneins 1 are involvement in metallic nanoparticles detoxification.